2013
DOI: 10.1590/s1415-790x2013000300021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the level of knowledge and compliance with standart precautions and the safety standard (NR-32) amongst physicians from a public university hospital, Brazil

Abstract: Brazil is the first country in the world to have broad coverage standard (NR-32) focused on protecting health workers exposed to biological risks. This study evaluated the degree of knowledge of the NR-32 Standard and the level of knowledge and compliance with the standard precautions. A cross-sectional study was conducted with 208 randomly selected health professionals; 93 of them were residents and 115 were physicians at a Brazilian Clinical Hospital. To collect information, the participants were interviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 24 publications
3
15
1
9
Order By: Relevance
“…Our findings are similar to a study in Hong Kong and Brazil where as high as 71% rate of compliance with SPP was reported. 8,18 Average knowledge of an infectious disease in this study was 26.27 (±6.6) which is low compared to what is acceptable. However, when these scores were correlated with participants SPP the result was statistically significant (r = 0.485, p<0.05).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Our findings are similar to a study in Hong Kong and Brazil where as high as 71% rate of compliance with SPP was reported. 8,18 Average knowledge of an infectious disease in this study was 26.27 (±6.6) which is low compared to what is acceptable. However, when these scores were correlated with participants SPP the result was statistically significant (r = 0.485, p<0.05).…”
Section: Discussioncontrasting
confidence: 61%
“…Studies have reported several modifiable factors to be associated with SPP. 1,[16][17][18] However, few studies have explored the role of these factors in Nigeria. With proper investigation these can serve as a blueprint for administrators, decision makers and government officials when designing and implementing intervention programs.…”
Section: Introductionmentioning
confidence: 99%
“…Marital status was also among the significant predictors of compliance with the universal precautions (La- Rotta et al, 2013). Married doctors show better compliance with the SP than single professionals.…”
Section: Sociodemographicmentioning
confidence: 95%
“…3,4 A fim de minimizar o risco de transmissão das infecções, as precauções padrão (PP) foram criadas e estabelecidas nos serviços de saúde, as quais compreendem um conjunto de práticas preventivas aplicadas no atendimento a todos os pacientes. [4][5][6] No entanto, para que tais recomendações sejam efetivas na prática, é necessário que o trabalhador da área da saúde adote tais comportamentos durante a realização de procedimentos assistenciais, o que exige do profissional motivação, conhecimento técnico científico e a manutenção de atitudes adequadas. 7 Embora aderir as PP signifique aderir a condutas preventivas, estudos demonstram índices insatisfatórios de adesão, como exemplos podem ser citados o uso inadequado de Equipamentos de Proteção Individual (EPIs), a prática frequente do reencape de agulhas, além da variação dos níveis de adesão de acordo com a categoria profissional.…”
Section: Introductionunclassified
“…7 Embora aderir as PP signifique aderir a condutas preventivas, estudos demonstram índices insatisfatórios de adesão, como exemplos podem ser citados o uso inadequado de Equipamentos de Proteção Individual (EPIs), a prática frequente do reencape de agulhas, além da variação dos níveis de adesão de acordo com a categoria profissional. 4,[6][7][8][9][10] Em uma pesquisa realizada nas unidades públicas odontológicas do município de Araçatuba-SP, observou-se que a grande maioria das agulhas apresentavam-se reencapadas em um ou nos dois lados. 10 No intuito de explicar os níveis de adesão às PP entre profissionais da saúde e os motivos que os levam a cumprir tais recomendações, modelos teóricos sobre adesão às PP foram desenvolvidos.…”
Section: Introductionunclassified